Seize and hold master strokes on the battlefield - Perrett, Bryan
The twentieth-century advent of the motorised battlegroup transformed what used to be a comparatively rare event - the coup de main - into an essential element of attack. Speed, surprise and firepower favour the small unit able to take the initiative against an unprepared enemy, and that is the central theme of this book: eleven such actions, ranging from central Europe in 1916, through the Second World War to Vietnam in 1965, capturing the thrill of the moment when the small motorised force breaks through enemy defences to reach its improbable target. This is aggressive warfare at its sharpest, and makes for compulsive reading.